2017
DOI: 10.1007/s00284-017-1375-y
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antimicrobial Activity Between the Broad Spectrum Bacteriocin Garvicin KS and Nisin, Farnesol and Polymyxin B Against Gram-Positive and Gram-Negative Bacteria

Abstract: The increasing emergence of antibiotics resistance is of global concern. Finding novel antimicrobial agents and strategies based on synergistic combinations are essential to combat resistant bacteria. We evaluated the activity of garvicin KS, a new bacteriocin produced by Lactococcus garvieae. The bacteriocin has a broad inhibitory spectrum, inhibiting members of all the 19 species of Gram-positive bacteria tested. Unlike other bacteriocins from Gram-positive bacteria, garvicin KS inhibits Acinetobacter but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…These findings here indicated that synergistic interaction between the two bacteriocins could be due to their different mode of action against target bacteria. One of them could be involved in pore formation/disruption of the outer cell membrane allowing access of the other bacteriocin in target cells as also suggested by Chi and Holo [8]. The mechanism of action of plantaricin LD4 is not exactly known, but our recent findings suggest that enterocin LD3 causes membrane disruption and enters inside the cells interacting with nucleic acids [17].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These findings here indicated that synergistic interaction between the two bacteriocins could be due to their different mode of action against target bacteria. One of them could be involved in pore formation/disruption of the outer cell membrane allowing access of the other bacteriocin in target cells as also suggested by Chi and Holo [8]. The mechanism of action of plantaricin LD4 is not exactly known, but our recent findings suggest that enterocin LD3 causes membrane disruption and enters inside the cells interacting with nucleic acids [17].…”
Section: Discussionsupporting
confidence: 56%
“…Bacteriocins are ribosomally synthesized antimicrobial peptides produced by bacteria exhibiting narrow spectra of activity against related species, whereas others display broader activity spectra against unrelated species [7]. In particular, most bacteriocins from lactic acid bacteria (LAB) have been attractive as potential natural antimicrobials due to the non-toxic nature of the compounds [8]. Although, bacteriocins are mostly non-toxic and considered safe, exceptions do exist; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro ability of garvicin KS to eradicate S. aureus biofilms is strain-dependent and is not augmented by micrococcin P1 Previous reports indicated that garvicin KS is effective in inhibiting the growth of S. aureus in liquid culture 42 , whereas micrococcin P1 has recently been regarded as a promising therapeutic alternative to antibiotics against MRSA and mycobacterial infections 43,44 . The antimicrobial potential of these bacteriocins, however, has never been assessed on clinically relevant S. aureus strains and, moreover, in a biofilm setting.…”
Section: Resultsmentioning
confidence: 99%
“…Different reports have established the main advantages and synergistic actions of LAB-bacteriocins with other biomolecules. These are the case of enterocin AS-48 and ethambutol against Mycobacterium tuberculosis (Aguilar-Pérez et al, 2018), nisin and citric acid against Staphylococcus aureus and Listeria monocytogenes (Zhao et al, 2017), nisin and beta-lactams against Salmonella enterica serovar Typhimurium (Rishi et al, 2014; Singh et al, 2014), and Garvicin KA-farnesol against a set of Gram-positive and Gram-negative bacteria (Chi and Holo, 2018). Orally administration of these substances is a challenge because of their enzymatic degradation.…”
Section: Pathogen Inhibitionmentioning
confidence: 99%